Sounding the Depths: Tradition and the Voices of History. 2011. Victor Grauer. Selfpublished via CreateSpace. Illustrations at http://soundingthedepths.blogspot.com/. 294pp. - Tracey, Andrew (International Library of African Music, 2012)
pages: 188-189
Keywords: African Music